2019
DOI: 10.1055/s-0039-1694982
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Obesity on Oxytocin Requirements to Achieve Vaginal Delivery

Abstract: Objective Our objective was to determine if obese women are more likely to require oxytocin rates > 20 mU/min to achieve vaginal delivery, compared with normal weight women. Study Design This is a retrospective cohort study of deliveries at the MedStar Washington Hospital Center and MedStar Georgetown University Hospital. Results There were 4,284 births included in the analysis. Thirty-three per cent of deliveries were among women classified as overweight (body mass index [BMI] 25–29.9 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Therefore, compared with the former ones, the dose of OT medication was more strictly limited in this group [13] . This study also found that the history of childbirth, BMI, and labor analgesia were independent factors affecting the OT medication, which was consistent with the results of the study by Adams, MD et al [14][15] . The possible reason was that the obesity, labor analgesia, and other factors would have inhibited the contractile ability of the uterine smooth muscle, requiring the increase of the exogenous OT dose for the OT receptors in vivo to enhance the contractions.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, compared with the former ones, the dose of OT medication was more strictly limited in this group [13] . This study also found that the history of childbirth, BMI, and labor analgesia were independent factors affecting the OT medication, which was consistent with the results of the study by Adams, MD et al [14][15] . The possible reason was that the obesity, labor analgesia, and other factors would have inhibited the contractile ability of the uterine smooth muscle, requiring the increase of the exogenous OT dose for the OT receptors in vivo to enhance the contractions.…”
Section: Discussionsupporting
confidence: 92%
“…17,22 They were also more likely to require higher dose of oxytocin infusion rate and longer duration of oxytocin exposure to achieve vaginal delivery. 34,35 Our study could not find the specific reason for this, it may be due to the fact that all our cases were spontaneous labour with no cases with induced labour that will usually also need augmentation.…”
Section: Progress Of Labourmentioning
confidence: 77%
“…This could be due to; maternal obesity is related with a lower bishop score, women with lower bishop scores are at greater risk for failed induction [ 41 ]. In addition, to achieve vaginal delivery, obese women require more concentration, higher doses, and longer duration of exposure of uterotonics medication, using similar protocol and guidelines on labor induction for all women with different BMI to end up with higher failure rate among obese women [ 44 , 45 ]. The current study has been shown that uterine contractility impairment is higher among morbid obesity women; uterine contractility dysfunction might lead to failed induction [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Women whose newborn birth weight ≥ 4000 g were 2 times more likely to have failed induction as compared with women whose newborn birth weight was 2500–3900 g. This study is supported by the previous studies [ 16 , 39 ]. This might happened due to the mean birth weight of neonates were higher among women who had greater BMI [ 44 ], larger BMI leads to lower bishop scores, and failed induction of labor [ 41 ].…”
Section: Discussionmentioning
confidence: 99%